The facile detection and micromechanism of ATMP and DTPMP by fluorescence sensor based on nitrogen-doped carbon nanomaterials. (November 2022) - Xie, Xingen; Feng, Shasha; Lei, Wu; Xia, Mingzhu; Wang, Fengyun; Ni, Yue
Abstract: In the present work, the N-doped fluorescent carbon nanomaterials (NCMs) were prepared. Fe 3+ quenched the fluorescence of NCMs effectively, while the addition of different concentrations of ATMP or DTPMP can restore the fluorescence intensity of NCMs to different degrees. Therefore, the Fe-NCMs fluorescent probe can quantitatively detect ATMP or DTPMP, and the detection limit (LOD) of ATMP and DTPMP was 0.479 μΜ and 0.254 μΜ, respectively. The fluorescence quenching mechanism of NCMs by Fe 3+ was revealed by UV–vis absorption spectra and the fluorescence lifetime analysis, the results showed that the fluorescence quenching was a combination of static and dynamic quenching. Moreover, based on Density Function Theory (DFT) calculation, basin analysis, topology analysis of atoms in molecules (AIM), electron localization function (ELF) analysis, and bond order density (BOD) analysis were firstly combined to reveal the difference in fluorescence restoration degree between the two organic phosphonates on Fe-NCMs. The detection mechanism of ATMP and DTPMP by Fe-NCMs was explained from a microscopic point of view. Highlights: Fe-NCMs were first applied in the detection of organophosphates. Fe-NCMs had high selectivity and sensitivity for ATMP and DTPMP. The micro-mechanism of fluorescence detection was revealed. Wave function analysis based on quantum chemistry theory was first applied.